Félix Hernández Giménez und die Erhaltung der Grossen Moschee von Córdoba - Giese, Francine (Madrider Mitteilungen, 2020)
On the occasion of the fortieth jubilee of Félix Hernández Giménez’s death (Barcelona 1889 – Córdoba 1975) this paper considers his intervention on the Great Mosque in Córdoba, commemorating the importance of his work as conservator of the Sixth Zone and highlighting his contribution within the Spanish heritage debate of the twentieth century. His work on the foundations of the prayer hall and the walls of this Mosque evidence his position against the ›escuela restauradora‹, mainly influenced by the restoration ideology of Violletle- Duc (1814–1879). Between 1930 and 1975 Hernández Giménez opposed this out-dated approach and advocated for the continuation of the pro-conservation policy of the 1920s and 1930s, thus standing apart from most of his colleagues. Even if his importance in this context was until recently still underestimated, it now appears beyond all question that his scientific approach, based on the theories of the Italian architect Camillo Boito (1836–1914), induced an absolutely necessary change of paradigm. Whereas his predecessor in Córdoba, the acclaimed Ricardo Velázquez Bosco (1843–1923), tried to renovate the epidermis of the building by means of spectacular reconstructions, Hernández Giménez confined his works to the protection and bracing of the monument’s infirm skeleton, thus making an essential contribution to the preservation of the Great Mosque of Córdoba.